2017
DOI: 10.24265/liberabit.2017.v23n1.07
|View full text |Cite
|
Sign up to set email alerts
|

Is experience in the public sector associated with Big Five personality aspects?

Abstract: The hypothesis that employees with experience in the public sector differ in personality aspects from those with less or no experience, suggested by the concept of personorganization fit, was tested among 711 participants in executive extension courses of a Peruvian university who filled-in the Big Five Aspect Scales. Whereas significant differences in various personality aspects were observed along age and between males and females, public sector experience only predicted greater Openness. Women outperformed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
3
0
2
Order By: Relevance
“…However, there is only little evidence on the links between higher-order personality traits and employee selection into the public and private sectors. The few studies that have explored this dimension of occupational sorting have found that women in the public sector tend to be more open (in the Big Five sense) than women in the private sector (León, 2017) and that public sector employees may be more extroverted (Maczulskij, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is only little evidence on the links between higher-order personality traits and employee selection into the public and private sectors. The few studies that have explored this dimension of occupational sorting have found that women in the public sector tend to be more open (in the Big Five sense) than women in the private sector (León, 2017) and that public sector employees may be more extroverted (Maczulskij, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it would be convenient to work on a modified version of the Organizational Cynic Scale because the content of the items and their underlying structure may not reflect the wide range of manifestations of organizational cynicism, such as sabotage, errors regarding coalitions, and power groups, lowering the pace of work, among others (Saravia, 2015). Likewise, more studies on organizational cynicism should be carried out concerning variables such as personality (León, 2017) and values (Sinha et al, 1993) in order to promote an improvement in the performance of labor, and work well-being, based on organizational behavior (Bravo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Much less is known on the links between higher‐order personality traits and employee selection into the public and private sectors. The few studies that have explored this dimension of occupational sorting have found that females in the public sector tend to be more open (in the Big Five sense) than those in the private sector (León, 2017) and that teachers in the public sector report lower levels of conscientiousness and higher levels of openness to new experiences (Dohmen & Falk, 2010).…”
Section: Contextual Frameworkmentioning
confidence: 99%